2001
DOI: 10.1046/j.1460-9592.2001.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral midazolam premedication on the awakening concentration of sevoflurane, recovery times and bispectral index in children

Abstract: There were no significant differences between groups in awakening time, sevoflurane or N2O awakening concentrations, time to PACU discharge, time to hospital discharge or in BIS I and BIS E measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
0
12
1
1
Order By: Relevance
“…The mean BIS awake value of 69 was low compared with those reported in other pediatric studies, which are frequently about 80 (2–4,8,9). In fact our BIS awake was in the same range as preawakening BIS values seen in other studies (4,9), probably because we recorded the BIS value averaged over the 30 s preceding awakening.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The mean BIS awake value of 69 was low compared with those reported in other pediatric studies, which are frequently about 80 (2–4,8,9). In fact our BIS awake was in the same range as preawakening BIS values seen in other studies (4,9), probably because we recorded the BIS value averaged over the 30 s preceding awakening.…”
Section: Discussioncontrasting
confidence: 67%
“…Brosius et al. showed variability of BIS values in children during equilibration of 3% sevoflurane in 60% N 2 O/40% O 2 (3), as did Denman et al. when using steady‐state PE sevo levels to study dose–effect relationships between PE sevo and BIS (2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One study in children age 1-10 yr found no large effects on BIS at awakening or at set sevoflurane concentrations. 6 The same authors reported no effect on intraoperative BIS but a lower BIS on awakening in children aged 10-18 yr. 8 Rodriguez and colleagues 7 reported the opposite: a lower value prearousal in those who had received midazolam. However, this result is confounded by the increased use of sedation in younger children.…”
Section: Discussionmentioning
confidence: 91%
“…Premedication was with paracetamol, and midazolam if indicated. In theory midazolam may affect the EEG, however previous studies have not demonstrated any affect of midazolam premedication on the relationship between EEG and sevoflurane concentration during anesthesia or the relation ship between EEG and awakening (3,9). Induction of anesthesia was with sevoflurane, with or without nitrous oxide and the trachea was intubated with or without atracurium.…”
Section: Protocolmentioning
confidence: 99%